Ecofriendly and cost-effective composites of titanium slag and carbonyl iron for lightweight and tunable microwave absorption. Issue 7 (1st April 2023) - Man, Qikui; Zhuang, Xueheng; Lei, Zhenkuang; Zhu, Shiqi; Pan, Lining; Gao, Yu; Tan, Guoguo
Abstract: For obtaining the ecofriendly microwave absorbing composites, flake carbonyl iron was mixed to the flotation carbon waste of titanium slag by ball-milling processes. The composites of 4 h ball-milling present excellent microwave absorbing performance of minimum reflected loss (RL) of −54.9 dB at 7.8 GHz with thickness of 2.6 mm. The same composites provide the performance of RL < −10 dB with the thickness from 1.2 mm to 5 mm at corresponding matching frequency from 3.3 GHz to 18 GHz. It means that the absorbing peak can be tunable at the wide frequency range with only adjusting the thickness. The strong absorbing intensity and wide tunable frequency range are attributed to the proper impedance matching of dielectric property from flotation carbon waste of titanium slag and magnetic property from carbonyl iron. Also, this work provides a research approach for handling industrial waste which contains carbon.